(untitled) (Research, Society and Development, 2023)
The objective of the present work was a bibliographical review about the aspects related to paresthesia during endodontic treatment, discussing the clinical signs presented, etiology, diagnoses, and possible treatments. To formulate the work, 23 articles were selected, which were published in full, from 2007 to 2022 in Portuguese and English. Paresthesia associated with endodontic treatment occurs because of overinstrumentation, overfilling, periapical infections, extravasation of irrigating solutions and during anesthesia. The main signs and symptoms presented are intense pain, burning sensations, itching and changes in sensitivity to cold or heat. According to the studies found, it was concluded that, due to the low incidence, information on the subject is still scarce, and there is no defined treatment protocol for cases of paresthesia involving Endodontics. However, it is known that the patient’s clinical history, the evolution of symptoms, detailed anamnesis, neurosensitivity tests and imaging exams facilitate the diagnosis and help with successful treatment. It is understood that it is necessary to cover studies in this area, where prevention is associated with adequate planning of the procedure, correct use of materials, knowledge of the apical and anatomical limits.